2011
DOI: 10.2350/09-11-0748-cr.1
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux Disease and Sudden Infant Death: Mechanisms behind an Under-Recognized Association

Abstract: We present 4 cases of sudden infant death in which we believe that gastroesophageal reflux (GOR) was a contributory, if not a causative, factor. Two of our patients had documented GOR reflux disease during life, and all 4 cases showed histologic evidence of GOR. No other cause of death was identified in any of the patients. Gastroesophageal reflux can cause sudden death in a vulnerable infant during a critical period of development through failure of "autoresuscitation" mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…We believe that esophageal peristalsis helps in the clearance of the noxious stimulus, and EPSR may prevent SER. Studies suggest that acid reflux of gastric contents causes apnea in animals or human infants (45), and GER is associated with SIDS (1,35,45). In addition, it has been found that sleep is associated with decreased swallowing and longer esophageal acid clearance time (33).…”
Section: Discussionmentioning
confidence: 99%
“…We believe that esophageal peristalsis helps in the clearance of the noxious stimulus, and EPSR may prevent SER. Studies suggest that acid reflux of gastric contents causes apnea in animals or human infants (45), and GER is associated with SIDS (1,35,45). In addition, it has been found that sleep is associated with decreased swallowing and longer esophageal acid clearance time (33).…”
Section: Discussionmentioning
confidence: 99%
“…35,52 Similarly, immaturity of vagal irritant reflexes has been implicated as a cause for silent aspiration and apnoea in infants born preterm. 71,72 It has been proposed that laryngeal chemoreflex may play a role in some cases of SIDS 35,52 ; 14% of SIDS cases have evidence of aspiration. 70 Gastro-oesophageal reflux is common in the first months of postnatal life, peaking at 3 to 4 months.…”
Section: The Hippocampus Seizures and Apnoeamentioning
confidence: 99%
“…2 Gastro-oesophageal reflux is also associated with sudden death. 71,72 It has been proposed that laryngeal chemoreflex may play a role in some cases of SIDS 35,52 ; 14% of SIDS cases have evidence of aspiration. 73…”
Section: Sensory Afferents From the Upper Airway: Oxygenconserving Rementioning
confidence: 99%
“…This spontaneous aspiration caused by gastroesophageal reflux, including steps of relaxation of esophageal sphincters, suppression of upper airway protective reflexes, and terminal inspiratory efforts, occurs even among non-resuscitated corpses as a terminal event [ 27 ]. Terminal gasping and autoresuscitation are thought to generate aspiration from the gastroesophageal route [ 14 , 28 , 29 ]. It is noteworthy that the presence of gastric contents in the airway does not invariably imply the occurrence of antemortem fatal aspiration [ 26 ].…”
Section: Discussionmentioning
confidence: 99%